ANALISIS EFEKTIVITAS PERENCANAAN DAN EVALUASI PROGRAM KESEHATAN DALAM MENINGKATKAN DERAJAT KESEHATAN MASYARAKAT - Anggun syahfira; Fitri Salsabila; Dewi Agustina; Salsa Ayudi Tila Simangunsong; Alya Nabila Putri; Asimah Mika Gracella Lamtio Siahaan; Linda jernih hati Daeli; Nurhayati Telaumbanua; Andini Febri Astuti; Nabilla Widya Ningsih; Hilsa Ananta Siregar; Sofia Rahma; Ani Sahara (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effectiveness of planning and evaluation of health programs in improving public health status. The background of this research is based on the existence of several issues in the implementation of health programs, such as inaccurate targeting, limited resources, and low effectiveness of outcomes. The method used is a qualitative approach through a literature study based on scientific journals, books, and official reports from the last five years. The results show that data-driven and community-based health program planning improves targeting accuracy and the quality of health services. In addition, systematic and periodic evaluation plays an important role in identifying program weaknesses and supporting continuous improvement. The integration of planning and evaluation has been proven to enhance overall program effectiveness. In conclusion, proper planning and continuous evaluation are key factors in improving public health status optimally.